Fracture liaison service utilising an emergency department information system to identify patients effectively reduce re-fracture rate is cost-effective and cost saving in Western Australia - Inderjeeth, C.A.; Raymond, W.D.; Geelhoed, E.; Briggs, Andrew; Oldham, D.; Mountain, D. (WILEY, 2022)
Objectives: To assess the benefits of the Emergency Department Information System (EDIS)-linked fracture liaison service (FLS). Methods: Patients identified through EDIS were invited to attend an FLS at the intervention hospital, the Sir Charles Gairdner Hospital (SCGS-FLS). The intervention group was compared to usual care. Retrospective control (RC) at this hospital determined historical fracture risk (SCGH-RC). Prospective control (PC) was from a comparator, Fremantle Hospital (FH-PC). The main outcome measures were cost-effectiveness from a health system perspective and quality of life by EuroQOL (EQ-5D). Bottom-up cost of medical care, against the cost of managing recurrent fracture (weighted basket), was determined from the literature and 2013/14 Australian Refined Diagnosis Related Groups (AR-DRG) prices. Mean incremental cost-effectiveness ratios were simulated from 5000 bootstrap iterations. Cost-effectiveness acceptability curves were generated. Results: The SCGH-FLS program reduced absolute re-fracture rates versus control cohorts (9.2–10.2%), producing an estimated cost saving of AUD$750,168–AUD$810,400 per 1000 patient-years in the first year. Between-groups QALYs differed with worse outcomes in both control groups (p < 0.001). The SCGH-FLS compared with SCGH-RC and FH-PC had a mean incremental cost of $8721 (95% CI −$1218, $35,044) and $8974 (95% CI −$26,701, $69,929), respectively, per 1% reduction in 12-month recurrent fracture risk. The SCGH-FLS compared with SCGH-RC and FH-PC had a mean incremental cost of $292 (95% CI −$3588, $3380) and −$261 (95% CI −$1521, $471) per EQ-5D QALY gained at 12 months respectively. With societal willingness to pay of $16,000, recurrent fracture is reduced by 1% in >80% of patients. Conclusions: This simple and easy model of identification and intervention demonstrated efficacy in reducing rates of recurrent fracture and was cost-effective and potentially cost saving.